Impact of anti-PLK1 siRNA-containing F3-targeted liposomes on the viability of both cancer and endothelial cells - Gomes-da-Silva, Lígia C. (2013)
We have previously described the development of novel sterically stabilized F3-targeted pH-sensitive liposomes, which exhibited the ability to target both cancer and endothelial cells. Herein, the therapeutic potential of those liposomes was assessed upon encapsulation of a siRNA against a well-validated molecular target, PLK1. Treatment of prostate cancer (PC3) and angiogenic endothelial (HMEC-1) cells with F3-targeted liposomes containing anti-PLK1 siRNA resulted in a significant decrease in cell viability, which was mediated by a marked PLK1 silencing, both at the mRNA and protein levels. Furthermore, pre-treatment of PC3 cells with F3-targeted liposomes containing anti-PLK1 siRNA enabled a 3-fold reduction of paclitaxel IC50 and a 2.5-fold augment of the percentage of cancer cells in G2/mitosis arrest, which ultimately culminated in cell death. Overall, the F3-targeted nanocarrier containing an anti-PLK1 siRNA might constitute a valuable system for prostate cancer treatment, either applied in a single schedule or combined with conventional chemotherapy.